2013
DOI: 10.1515/erj-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Emotional Nexus in Cogent Family Business Archetypes

Abstract: This article aims at offering a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 64 publications
3
35
0
3
Order By: Relevance
“…We found that during successor installation, some participants engage in an emancipation process, motivated by self-differentiation and self-promotion motives, mainly by using confrontational strategies. Emancipation seems to be of major importance for successors from enmeshed family businesses, because of their higher need of self-differentiation as regards the incumbent, which extends prior studies on enmeshed, balanced and disengaged family businesses (Labaki et al, 2013). We showed that during successor installation, the self-differentiation motive might become so intense that successors take the risk of revealing their negative feelings by using confrontational strategies and showing incumbents that they are different from them.…”
Section: Outcomes Of Managing Ambivalent Emotions: Legitimacy and Emasupporting
confidence: 83%
See 3 more Smart Citations
“…We found that during successor installation, some participants engage in an emancipation process, motivated by self-differentiation and self-promotion motives, mainly by using confrontational strategies. Emancipation seems to be of major importance for successors from enmeshed family businesses, because of their higher need of self-differentiation as regards the incumbent, which extends prior studies on enmeshed, balanced and disengaged family businesses (Labaki et al, 2013). We showed that during successor installation, the self-differentiation motive might become so intense that successors take the risk of revealing their negative feelings by using confrontational strategies and showing incumbents that they are different from them.…”
Section: Outcomes Of Managing Ambivalent Emotions: Legitimacy and Emasupporting
confidence: 83%
“…Whereas prior research attributes emotions to the family system only (Bee and Neubaum, 2014;Carlock and Ward, 2001;Combs et al, 2019;Fleming, 2000), we show that ambivalent emotions occur at the intersection of both the family and the business systems because the family-business overlap triggers role conflict. Answering prior calls to examine emotions at the nexus of the family and the business systems Labaki et al, 2013), we find that these emotional ambivalences mostly occur in enmeshed family businesses. In disengaged family businesses, there are less occasions of mixed emotions, according to the accounts of successors.…”
Section: Emotional Ambivalence Of Successors In Response To the Paradmentioning
confidence: 66%
See 2 more Smart Citations
“…Using Bowen’s (1978) theory, Distelberg and Sorenson (2009) considered the first generation of family firms to be characterized by enmeshment between the family and business systems. Labaki, Michael‐Tsabari, and Zachary (2011) suggested a typology based on different levels of enmeshment between the two systems, with the first generation typically tending to be rigidly enmeshed. Taking into account the inherent overlap between family and firm during the first generation (Tagiuri & Davis, 1996), we argue that the business family in the early stages is rigidly enmeshed, allowing and enabling further enmeshment between the family and the business as a whole.…”
Section: Implications For Families and The Functioning Of Family Firmsmentioning
confidence: 99%